Detection of Heavy Mineral Elements in Some Types of coffee that taken from different sources (Latakia University Journal -Biological Sciences Series, 2020)
The aim of this research was to evaluate the degree of contamination of different types of coffee available in the domestic market imported from Brazil and India with the elements of lead and copper. Sampling (20 samples) took place before roasting (raw) and after roasting, and then samples were digested with royal water (65% concentrated nitrogen acid and acid Water chlorine 70%), was then estimated using the atomic absorption device at the Marine Research Institute and the amount was estimated as mg / kg. The results of the analysis showed that the lead values ​​were in all samples of different types and sources less than the upper limit allowed in the Syrian standard, while copper values ​​in the Brazilian type (raw, roasted, ground) were (8.04, 10.34, (9.77 mg / kg, respectively). Within the permissible limits according to the Syrian standard, and in the Indian type (raw, roasted, ground) (9.60, 12.42, 11.25) mg / kg, respectively, is higher than the permissible limit in roasted and ground according to the Syrian standard.